Does Customer Relationship Management and Customer Satisfaction affect PT. JNE Pusat Banjarmasin Customer Loyalty? - Huliyyah; Faqih El Wafa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the development of competition in the business world, and especially companies engaged in the service sector. It requires companies to always survive in managing their business by maintaining good relationships with customers and increasing customer satisfaction. Therefore, companies carry out marketing strategies often referred to as CRM (Customer Relationship Management) and customer satisfaction to maintain customer loyalty. This type of research is field research using quantitative research methods. The results showed that the CRM variable partially did not affect customer loyalty at PT. JNE Pusat Banjarmasin, with the t-test results where the t hitung is 0.693 <t tabel 2.020 and the value of Sig. 0.492 > 0.05. At the same time, the variable customer satisfaction has a positive and significant effect partially on customer loyalty at PT. JNE Center Banjarmasin, with the t-test results where t count is 4.839 > t table 2.020 and the Sig level is 0.000 <0.05. For the F test, the CRM variable and customer satisfaction influence customer loyalty at PT. JNE Pusat Banjarmasin, where the Fcount value is 37.852 > Ftable 4.07, and the Sig. 0.000 < 0.05.